RANCANG BANGUN KWH METER PULSA PADA KAMAR KOST BERBASIS IoT ESP32 DAN WEB - Ponciano Hipolito; Priyandoko , Gigih; Effendy, Dedi Usman (JASEE Journal of Application and Science on Electrical Engineering, 2024)
Internet of Things (IoT) is one of the new trends in the world of technology. IoT is a concept that aims to expand the benefits of continuously connected internet connectivity. The access capabilities of IoT can be unlimited thanks to IoT devices that are always connected to the internet, so they can be accessed and used anytime and anywhere. KWH (Kilo Watt Hour) meter is an instrument that has the main function of measuring electrical energy. The KWH meters that are widely known by the general public are conventional KWH meters which have limitations. This IoT technology makes it possible to monitor electrical quantities. In the final project research, an electrical quantity monitoring system was created which can provide information on monitoring results via a web page so that it can be observed in real time. Based on the problems above, research was carried out to design equipment using the concept of the Internet of Things (IoT) with the aim of providing information about the amount of electrical power used and conveyed to boarding room users via a website containing digital KWH meter counts in each boarding room. This information is power usage and the number of electricity credits in each boarding room. By creating this tool, it is hoped that it can provide time efficiency and make it easier for boarding house residents and boarding house owners to monitor and find out the costs incurred. Keywords: IoT, LCD, Firebase, ESP32, KWH meter